"(Un)informed College and Major Choice": Verification in an alternate setting. (August 2016) - Huntington-Klein, Nick
Highlights: I evaluate Hastings et al. model of costly information about college. I test predictions of the model using subjective expectations data from the United States. I find strong support for two predictions of the model, and weak support for another two. The costly information model likely has broad applications for the study of education. Abstract: In their recent paper "(Un)informed College and Major Choice: Evidence from Linked Survey and Administrative Data, " Hastings, Neilson, Ramirez, & Zimmerman (2016) provide an informal costly-information model, linking family background to students' beliefs about educational costs and benefits. They verify predictions of their model using a data set of beliefs about college institutions and majors among Chilean college applicants and students. I test some of those same predictions using a data set of beliefs about college institutions and different levels of college education among high school students in the United States. I verify their predictions, with some exceptions, supporting the use of their costly-search model.